Preliminary Studies on Liquiritin, Deoxyschizandrin, and Tanshinone II A as Potential Anti-Neurodegenerative Disease Agent: Determination by Reverse-Phase Liquid Chromatography in Tianwang Buxin Pills - Dan Xu; Sicen Wang; Xiaofang Hou; Changshan Sun (Journal of Analytical Methods in Chemistry)
Tianwang Buxin pill (TWBXP) is an ancient Chinese classic prescription. Liquiritin, deoxyschizandrin, and tanshinone II A are three bioactive components in TWBXP, which have been proven to be closely related to the therapy effect of neurodegenerative disease. Their contents are very low in TWBXP. In this study, we used a diode array detector (DAD) to perform a full wavelength scanning in order to choose a most suitable detection wavelength to establish an HPLC method for the simultaneous determination of these three components in TWBXP. Various chromatographic conditions were investigated to verify its applicability. Finally, a Kromasil C18 column (250 × 4.6 mm, 5 μm) thermostated at 30°C, mobile phase as 0.2% phosphoric acid solution (eluent A), and 0.1% phosphoric acid-acetonitrile solution (eluent B) were used. Both external standard method and internal standard method were used for quantification. The results showed that both methods were simple and convenient in operation without special pretreatment and exhibits excellent precision, repeatability (RSD < 3.0%), good linearity (R2 > 0.9990), and good recoveries (recovery value between 95% and 105%). Because of the low contents in samples, the internal standard method provided a better accurate result than the external standard method. The stability results showed the sample became stable within 24 hours at room temperature. The method provides a convenient and effective way for the quality control of TWBXP, and it can help the research about AD in the future.